2019
DOI: 10.1088/1757-899x/628/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, experimental investigation of jute fiber reinforced epoxy composites and hybrid composites

Abstract: A special type of jute fiber woven mat was introduced by a hand loom. Epoxy jute fiber composites were fabricated using the woven fiber mat. A series of jute-hybrid epoxy composites based on the arrangement of the direction of jute fibers, and additional material were introduced to ensure the elevated mechanical properties of the composites. Improved mechanical properties were found in some cases of hybrid epoxy composites. It is discussed that the mechanical behavior is related to the fiber orientation, types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…18 Only a few researchers have carried out studies on the effect of the stacking sequence on the tensile and flexural strength of hybrid composites. 22,23 In these studies, it was found that placing a relatively stronger fiber on the outside of the composite increases the flexural strength. It was also reported that the tensile strength increased with increasing fiber volume in the hybrid composite.…”
Section: Introductionmentioning
confidence: 99%
“…18 Only a few researchers have carried out studies on the effect of the stacking sequence on the tensile and flexural strength of hybrid composites. 22,23 In these studies, it was found that placing a relatively stronger fiber on the outside of the composite increases the flexural strength. It was also reported that the tensile strength increased with increasing fiber volume in the hybrid composite.…”
Section: Introductionmentioning
confidence: 99%
“…This process, known as hybridization, yields high-quality, cost-effective, and environmentally beneficial materials. 37 Few researchers [38][39][40][41] conducted investigations to evaluate the influence of the stacking sequence on the flexural and tensile strengths of composites manufactured in a hybrid manner. The implication of somewhat robust fibers to the surface of a material increases its tensile and flexural strength, as discovered.…”
Section: Introductionmentioning
confidence: 99%
“…23 The hybridization process would help to increase the strength of polymer matrix composites reinforced with different natural fibers and suitable filler materials may help improve the characteristics of composites then 10% glass fiber, 20% jute fiber, and 10% tea fiber achieved the optimum mechanical properties, it can be an alternative material for the pure glass fiber. [24][25][26][27] Ramprasath et al determined that both meta-heuristic and statistical methods were used to optimize the mechanical behaviors of coir fiber-reinforced vinyl ester composites with the addition of red mud particles. 28 Jayabal et al demonstrated the fiber pull-out began with natural fibers before moving on to glass fibers and an excellent interfacial bonding was created between the woven glass and polyester resin as opposed to the coir-polyester matrix using a scanning electron microscope (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…23 The hybridization process would help to increase the strength of polymer matrix composites reinforced with different natural fibers and suitable filler materials may help improve the characteristics of composites then 10% glass fiber, 20% jute fiber, and 10% tea fiber achieved the optimum mechanical properties, it can be an alternative material for the pure glass fiber. 2427 Ramprasath et al determined that both meta-heuristic and statistical methods were used to optimize the mechanical behaviors of coir fiber-reinforced vinyl ester composites with the addition of red mud particles. 28…”
Section: Introductionmentioning
confidence: 99%